Chinese Historical and Ethnographic Monument “Images of Tributaries of the Ruling Qing Dynasty”: the Background to the Creation and Socio-Cultural Significance - N. A. Samoylov; D. I. Mayatskiy (Научный диалог, 2019)
The article is devoted to the study of Chinese historical and ethnographic monuments “Images of tributaries” (“Zhi gong tu”). One of them - “Images of tributaries of the ruling Qing dynasty” (“Huang Qing zhi gong tu”) is mostly analyzed. The novelty of the study is in the fact that for the first time in Russian science a comprehensive review and analytical consideration of these works is presented. The relevance of the study is caused by the growing scientific interest of Russian and foreign scientists in imagological research, as well as poor knowledge of these monuments. The article restores the historical background and circumstances of the creation of the album “Images of tributaries of the ruling Qing Dynasty”. The codicological and structural-compositional descriptions of two copies of it are kept in the collection of old-printed Chinese books of the Scientific Library of St. Petersburg State University. The classification of the regions and peoples described in the album is given. The method of organizing the material is analyzed. The nature of the information reported about ethnic groups is revealed. The question of the multi-level content of the book is raised, and the importance of its comprehensive study using interdisciplinary approaches is noted. Particular attention is paid to the connection of the monument with the traditional foreign policy concepts of imperial China; the unique features of “Huang Qing zhi gong tu” are revealed.